2020
DOI: 10.5603/arm.a2020.0149
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Implications of Bronchial Lavage in Patients with Pleural Tuberculosis

Abstract: Introduction: The presence of Mycobacterium tuberculosis in a respiratory specimen is diagnostic in patients with pleural effusion. It is difficult to obtain sputum even after induction in these patients. An alternative method of acquiring respiratory specimens is via bronchial lavage. This study was undertaken to evaluate the diagnostic yield of acid-fast bacilli (AFB) smear, AFB culture, and Xpert assay of bronchial lavage fluid in the workup of pleural tuberculosis patients. Material and methods: All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…One (1.4%) study was conducted exclusively in HIV seropositive patients [ 43 ], while seven (9.5%) others included a variable number of such subjects [ 37 , 38 , 42 , 44 , 53 , 70 , 89 ]. There were no HIV seropositive patients in thirteen (17.6%) publications [ 30 , 47 , 63 , 73 , 74 , 76 , 78 , 79 , 83 , 84 , 88 , 92 , 96 ], while the remaining did not provide any information. Ten investigators thawed cryopreserved fluid samples for their tests [ 23 , 31 , 35 , 42 , 60 , 66 , 73 , 78 , 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…One (1.4%) study was conducted exclusively in HIV seropositive patients [ 43 ], while seven (9.5%) others included a variable number of such subjects [ 37 , 38 , 42 , 44 , 53 , 70 , 89 ]. There were no HIV seropositive patients in thirteen (17.6%) publications [ 30 , 47 , 63 , 73 , 74 , 76 , 78 , 79 , 83 , 84 , 88 , 92 , 96 ], while the remaining did not provide any information. Ten investigators thawed cryopreserved fluid samples for their tests [ 23 , 31 , 35 , 42 , 60 , 66 , 73 , 78 , 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 18 articles were included for meta‐analysis. 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 …”
Section: Resultsmentioning
confidence: 99%
“…The comparison of AFB positivity showed that bronchial aspirate/bronchoalveolar lavage produced the highest diagnostic yield (51.5%) as compared to endobronchial biopsy (37.3%), transbronchial lung biopsy (45.5%), and transbronchial needle aspiration (33%) (26). For patients with pleural TB, where it is difficult to obtain sputum even after induction in some patients, bronchial lavage AFB smear, culture, and the Xpert assay were positive in 9.5, 17.9, and 26.2% patients, respectively (27). Bronchial lavage provided an immediate diagnosis in 22 (26.2%) patients (27).…”
Section: Discussionmentioning
confidence: 98%
“…For patients with pleural TB, where it is difficult to obtain sputum even after induction in some patients, bronchial lavage AFB smear, culture, and the Xpert assay were positive in 9.5, 17.9, and 26.2% patients, respectively (27). Bronchial lavage provided an immediate diagnosis in 22 (26.2%) patients (27). Bronchial lavage, although not a surrogate to pleural biopsy, offers an additional approach to the early diagnosis of pleural TB in patients unable to produce sputum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation